(untitled) (CIPEEX, 2025)
The document aims to deepen the analysis of the international responsibility of States in Public International Law, considering fundamental rights, related duties, and the legal consequences of committing wrongful acts in the international sphere. The study seeks to clarify how the principles of sovereignty, equality, and development reconcile with the limitations imposed by the international legal system, which requires States to conduct themselves based on mutual respect and cooperation. The adopted method is essentially doctrinal and normative, based on sources of international law, such as the UN Charter, the Vienna Convention on Diplomatic Relations, multilateral treaties, as well as decisions of the International Court of Justice and established jurisprudence. This methodology allows for the systematization of central concepts and offers concrete examples of practical application. The results demonstrate that, despite sovereign autonomy, States are bound by fundamental duties, such as the duty of non-intervention, which extends to the political, military, and economic spheres, except in cases of self-defense, protection of human rights, and assistance to nationals abroad. It demonstrates that the violation of these duties entails international liability, which is structured around three elements: the commission of a wrongful act, the imputability of the State, and the existence of harm. The analysis emphasizes that reparation must be comprehensive, restoring the status quo ante, and may involve restitution, compensation, or indemnity, and that it should not be confused with sanctions, both criminal and moral. Furthermore, the document highlights the institution of diplomatic protection, a mechanism by which the State of origin assumes the claim of its injured nationals, transforming it into an international lawsuit, although its exercise depends on criteria such as nationality and exhaustion of domestic remedies. It concludes that the international liability of States constitutes a pillar of the global legal order, functioning as an indispensable means to prevent abuses of power, redress injustices, and ensure peace and cooperation among nations, reinforcing the idea that sovereign rights must be exercised in accordance with duties aimed at maintaining the international community as a whole.